Biomorphic Design of Age-Friendly Wearable Devices: Flexible Circuits and Self-Luminescent Display Interfaces Based on Vascular Bionic Structures - Zhang, Yingyu (EAI Endorsed Transactions on Pervasive Health and Technology, 2026)
With the accelerating aging of the global population, the importance of health monitoring and assistive technologies for the elderly is becoming increasingly prominent. This study aims to propose and validate a biomorphic design framework based on vascular biomimetic structures to address the challenges of mechanical adaptability, signal stability, and cognitive interaction in age-friendly wearable devices. Using microfluidic lithography and differential capillary self-assembly, a liquid metal flexible circuit with a fractal topology mimicking human microvasculature is constructed on a SEBS/TPU composite substrate. A biomimetic microhinge array is used to disperse stress, and micropits are laser-engraved on the surface to enhance breathability. The display interface, based on a poly(3,4-ethylenedioxythiophene) microcapsule array, combines electrochromic and photoluminescent effects to map parameters such as blood pressure and blood oxygen into dynamic fractal growth patterns. Experimental data show that the biomimetic circuit exhibits a resistance change of only 11.72% under a strain of only 15%, and the substrate stiffness pressure is 0.82±0.07 kPa, ensuring signal stability and comfortable wear during exercise. The user experience is significantly improved, with a low discomfort feedback rate of 7.2%. The conclusion shows that biomorphic design based on vascular bionic structure provides a suitable and systematic solution for the physiological adaptation and cognitive interaction of elderly-friendly wearable devices.